‘What was the comparative history of religion in seventeenth-century Europe (and beyond)? Pagan monotheism/Pagan animism, from T’ien to Tylor’ - Levitin, D (Brill, 2018)
When faced with the spectacular outpouring of seventeenth-century texts that seem to provide something that looks like the comparative history of religions, it is tempting to adopt one of two positions. One is condemnatory: the reduction of these texts to the ‘polemical’ contexts that inspired them. The other is celebratory: to announce that the seventeenth century witnessed the flowering of the ‘modern’ study of religion. The following investigation proposes an alternative approach, one that seeks to recover the historical specificity of the early modern comparative enterprise. It argues that the period did indeed see very large transformations to ideas about world religions, and that these ideas unquestionably transcended any polemical-political aims that underpinned them. On the other hand, what may sometimes look like ‘modern’ comparatism was in fact grounded in very pre-modern forms of engagement with the textual legacy of classical antiquity, early Christianity, and medieval natural theology. Around the late sixteenth century, European scholars came to realise that arguments for the similarity between pagan and Judaeo-Christian conceptions of the divine – arguments stemming from the Hellenistic Jews and the church fathers – were unreliable. Instead, they increasingly characterised pagan ‘theology’ as broadly animist. But this reading could be interpreted in two ways. One was to suggest that this animism concealed a latent monotheism, grounded in an imperfect recognition of the true deity as he could be predicated by analogical reasoning upon the natural world. The second view was that pagan animism was so fundamentally incompatible with Judaeo-Christian transcendentalism that it was better characterised as a monist atheism, akin to the theology of the earliest Greek philosophers (whose doctrines were also being reconsidered at this time). This debate involved a spectacular range of participants: late humanist scholars; Christian missionaries and their native interlocutors; pioneering natural philosophers; and the most important players the European respublica literaria. Gradually, the second view came to be dominant, to the extent that in the late seventeenth century, it offered Pierre Bayle a heuristic for the interpretation of all pagan religion, stretching from ancient Egypt to Japan; and from Greek philosophy to Neoconfucianism. Its influence continued long after, shaping the work of the orientalists of the eighteenth century, and the founding fathers of social anthropology, E.B. Tylor, in the nineteenth.